Labour market in Lithuania: gender situation - Guščinskienė, Jūratė; Čiburienė, Jadvyga (Business, Management and Economics Engineering, 2010)
The article analyses the situation of men and women in the labour market in the globalization and economic integration into the European Union conditions and demonstrates that gender equality under the current conditions and social life, politics and economy is becoming a political priority. The aim of the paper is: to analyze the situation of men and women in the labour market and its regulation; to study the respondents’ view on the situation of men and women in the labour market. Empirical study showed that 42% of women and 26% of men have never lost their jobs and the people who have, have men-tioned several reasons for this. Respondents, both women and men, generally lose work because of inadequate working conditions and the company’s bankruptcy. Meanwhile, the response of men’s and women’s opinion on the inequality/discrimination experience is different. According to women, involved in the study, in Lithuania they mostly experienced discrimination based on sex and age, while men consider to be most discriminated on grounds of sex, disability and age. Almost one fifth of the respondents have personally experienced discrimination themselves in the labour market because of sex.Article in Lithuanian.Darbo rinka Lietuvoje: moterų ir vyrų padėtis